ANALISIS KETEPATAN PASSING MAHASISWA UNIVERSITAS NEGERI MEDAN JURUSAN PJKR STAMBUK 2024 - Kudadiri, Dwi Irene; Br Pasaribu, Cintya Margaretta; Ginting, Fernando; Pasaribu, Rahmad Riski; Manalu, Nimrot (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to determine the level of passing accuracy among students of the Physical Education, Health, and Recreation (PJKR) Department, Class B, Stambuk 2024, Universitas Negeri Medan. Passing is considered one of the most essential basic techniques in football because it greatly influences teamwork effectiveness and game control. However, several students were still found to have inconsistent passing accuracy during learning activities and practical sessions. This research employed a quantitative descriptive approach using test and measurement methods. The sample consisted of 28 students, including 15 female students and 13 male students, selected through total sampling technique. Data collection was conducted using a football passing accuracy test instrument with predetermined scoring criteria. The results showed that the majority of students were categorized in the moderate and good categories. The average passing accuracy score obtained by the students indicated that the basic passing ability still requires improvement through continuous training and structured practice programs.